Identification of hub genes and their correlation with infiltration of immune cells in MYCN positive neuroblastoma based on WGCNA and LASSO algorithm - Chen, Ji; Sun, Mengjiao; Chen, Chuqin; Jiang, Bin; Fang, Yongjun (Frontiers in Immunology, 2022)
Background：The prognosis of MYCN positive NB is poor, and there is no targeted drug for N-myc at present. This study aims to screen out hub genes closely related to MYCN, analyze the relationship between hub genes and NB microenvironment, and provide basis for molecular targeted therapy of MYCN positive NB. Methods：We combined the microarray data of GSE45547 and GSE49710, screened the DEGs between MYCN positive and MYCN negative NB, performed WGCNA, Lasso regression and ROC analyses on the merged matrix, and obtained the hub genes related to MYCN. The distribution of each immune cell in NB microenvironment was analyzed by ssGSEA immune cell infiltration analysis, and the influences of hub genes on the distribution of each immune cell in the tumor microenvironment were analyzed. Results：Here were 880 DEGs including 420 upregulated and 460 downregulated genes in MYCN positive NB. Overlap of the DEGs and WGCNA networks identified four shared genes, namely, ZNF695, CHEK1, C15ORF42 and EXO1, as candidate hub genes in MYCN positive NB. Three core genes, ZNF695, CHEK1 and C15ORF42, were finally identified by Lasso regression and ROC analyses. The data of validation group and NB cell lines also confirmed that CHEK1, C15ORF42 and C15ORF42 were highly expressed in MYCN positive NB tissues and cell lines, and these three genes were closely related to the prognosis of children with NB. SsGSEA analysis showed that the distribution of immune cells in MYCN positive and MYCN negative NB microenvironment was different. ZNF695, CHEK1 and C15ORF42 were closely related to the status of immune cells Infiltration. Conclusion：Three genes closely related to the prognosis of children with MYCN positive NB were screened. There are differences between the microenvironment of MYCN positive and MYCN negative NB, and three hub genes have an impact on the distribution of immune cells in tumor microenvironment. This study provides potential prognostic markers and immunotherapy targets for MYCN positive NB.